RELIGIOUS MENTALITY OF BORYSLAV DEANERY PARISH POPULATION OF PEREMYŚL GREEK CATHOLIC DIOCESE (the 30s of the 20th century) - STETSYK , Yurii; VASYLIV, Pavlo (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to reveal the main manifestations regarding the religious mentality of Boryslav Deanery parish population of the Greek Catholic Diocese of Przemyśl in the 1930s. The research methodology is based on the work with manuscript documentary materials, analytical and synthetic criticism of sources was used to verify the information from them. The scientific novelty can be traced to the involvement of a significant array of documentary material from the church funds of the Greek Catholic Consistory of Przemyśl with the presentation of the latest scientific interpretations and views. Conclusions. The religious mentality of Boryslav Deanery parish population of the Greek Catholic Diocese of Przemyśl was built on the Christian principles of love, mercy, and mutual assistance. There have been established charitable societies at churches in order to provide material assistance to the poor, widows, orphans, and cripples. The сhurch brotherhoods organized the parish communities to maintain the churches. The religious societies of the Apostolic Prayer involved the most active believers in popularizing the spiritual practices of the Christians: daily prayers, monthly confession, and communion. The spread of the Catholic press among the parish population was to help oust the anti-Catholic sectarian publications. Encouraging the reading of faithful Christian literature contributed to the believers’ awareness in the basic teachings of the Catholic Church. The preaching work of the parish clergy was aimed at eradicating the influence of distorted teachings of the sectarian Christian communities. The socialist and communist ideas were spreading among the local labour migrants, aimed at undermining the authority of the church and promoting the atheistic ideology. Local priests directed their public and cultural and educational activities to combating these threatening anti-Christian movements, since the Deanery included the largest number of the parish centres (Boryslav, Tustanychi, Stebnyk), where industrial infrastructure was being built. There were organized regular spiritual retreats and long-term missions for the believers in the individual parishes among the workers with the Basilian monks’ involvement, which converted the apostates and raised the piety of the Christians. However, there were isolated cases of conflict between the parishioners and the parish priest, which had a negative impact on the Christian virtues and national education development. Key words: mentality; Christianity; Catholicism; society; brotherhood; recolactio; mission.